2020
DOI: 10.3390/ani11010059
|View full text |Cite
|
Sign up to set email alerts
|

Spiny-Cheek Crayfish, Faxonius limosus (Rafinesque, 1817), as an Alternative Food Source

Abstract: The aim of the study was to present a comprehensive characterisation of crayfish meat, which is crucial to assess its potential usefulness in the food industry. To this end, we assessed the yield, basic chemical composition (protein, fat, minerals), nutritional value (amino acid and fatty acid profiles, essential amino acid index (EAAI), chemical score of essential amino acids (CS), hypocholesterolaemic/hypercholesterolaemic ratio (h/H), atherogenicity (AI) and thrombogenicity (TI) indices), as well as culinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 103 publications
1
15
0
Order By: Relevance
“…Generally, AI and TI should be kept at low levels (<1.0 for AI and <0.5 for TI) [ 24 ]. The observed AI and TI of the crayfish meat were lower than those for other meats such as beef, lamb, pork, chicken and rabbit [ 23 ]. The authors revised the sentence: High level of n-3 PUFA, low n-3/n-6 ratio, AI and TI indicated that the meat of spiny crayfish could be considered as an alternative source of essential fatty acids and that regular consumption of crayfish meat has great potential for protecting against coronary disease [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, AI and TI should be kept at low levels (<1.0 for AI and <0.5 for TI) [ 24 ]. The observed AI and TI of the crayfish meat were lower than those for other meats such as beef, lamb, pork, chicken and rabbit [ 23 ]. The authors revised the sentence: High level of n-3 PUFA, low n-3/n-6 ratio, AI and TI indicated that the meat of spiny crayfish could be considered as an alternative source of essential fatty acids and that regular consumption of crayfish meat has great potential for protecting against coronary disease [ 22 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that crayfish meat is an excellent source of minerals, particularly calcium, sodium, potassium, copper, zinc, magnesium and iron [ 21 , 22 ]. In comprehensive literature reviews, only a few scientific studies have investigated spiny-cheek crayfish meat [ 23 , 24 , 25 ]. Thus, there is insufficient data that fully describes the safety, nutritive value and sensorial properties of spiny-cheek crayfish meat, which are a prerequisite for their exploitation and placement as a novel product in the market.…”
Section: Introductionmentioning
confidence: 99%
“…Only in the case of Cu was DRI exceeded, with the range from 88 to 164% of DRI. As confirmed by Śmietana et al ( 2021 ), the consumption of 100 g of chelae muscle of spiny-cheek crayfish from Lake Sominko covers 103.7 and 54.8% of the consumer’s daily demand for Zn and Ca, respectively. The consumption of 100 g of abdomen muscle mostly covers the demand for Zn (17.08%).…”
Section: Discussionmentioning
confidence: 64%
“…It has been proposed that crayfish muscle can be considered by the food industry as an alternative source of raw material (Śmietana et al 2021 ). According to these authors, the abdomen and chelae muscles can be a source of minerals, too.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Brenneis et al (2011) show, by means of an experimental approach that the native crayfish Pacifastacus leniusculus consumes and digests the NZMS, which could be an important food source for this species in areas invaded by the NZMS. Crayfish species are used as a source of food and disease control in many parts of the world (Gherardi, 2011;Nonaka, 2012;Heikal et al, 2018;Smietana et al, 2021). Thus, the NZMS may potentially increase the many ecosystem services reported for crayfish species (Gherardi, 2011), which can be important in aquatic ecosystems Fig.…”
Section: Effects On Native Faunamentioning
confidence: 99%